Drosulfakinin signaling encodes early-life memory for adaptive social plasticity - Jiwon Jeong; Kujin Kwon; Terezia Klaudia Geisseova; Jongbin Lee; Taejoon Kwon; Chunghun Lim (eLife)
Drosophila establishes social clusters in groups, yet the underlying principles remain poorly understood. Here, we performed a systemic analysis of social network behavior (SNB) that quantifies individual social distance (SD) in a group over time. The SNB assessment in 175 inbred strains from the Drosophila Genetics Reference Panel showed a tight association of short SD with long developmental time, low food intake, and hypoactivity. The developmental inferiority in short-SD individuals was compensated by their group culturing. By contrast, developmental isolation silenced the beneficial effects of social interactions in adults and blunted the plasticity of SNB under physiological challenges. Transcriptome analyses revealed genetic diversity for SD traits, whereas social isolation reprogrammed select genetic pathways, regardless of SD phenotypes. In particular, social deprivation suppressed the expression of the neuropeptide Drosulfakinin (Dsk) in three pairs of adult brain neurons. Male-specific DSK signaling to cholecystokinin-like receptor 17D1 mediated the SNB plasticity. In fact, transgenic manipulations of the DSK neuron activity were sufficient to imitate the state of social experience. Given the functional conservation of mammalian Dsk homologs, we propose that animals may have evolved a dedicated neural mechanism to encode early-life experience and transform group properties adaptively.